Preclinical evaluation of engineered L-asparaginase variants to improve the treatment of Acute Lymphoblastic Leukemia - Soumika Sengupta; Mainak Biswas; Khushboo A. Gandhi; Saurabh Kumar Gupta; Poonam B. Gera; Vikram Gota; Avinash Sonawane (Translational Oncology, 2024)
Introduction: Escherichia coli l-asparaginase (EcA), an integral part of multi-agent chemotherapy protocols of acute lymphoblastic leukemia (ALL), is constrained by safety concerns and the development of anti-asparaginase antibodies. Novel variants with better pharmacological properties are desirable. Methods: Thousands of novel EcA variants were constructed using protein engineering approach. After preliminary screening, two mutants, KHY-17 and KHYW-17 were selected for further development. The variants were characterized for asparaginase activity, glutaminase activity, cytotoxicity and antigenicity in vitro. Immunogenicity, pharmacokinetics, safety and efficacy were tested in vivo. Binding of the variants to pre-existing antibodies in primary and relapsed ALL patients’ samples was evaluated. Results: Both variants showed similar asparaginase activity but approximately 24-fold reduced glutaminase activity compared to wild-type EcA (WT). Cytotoxicity against Reh cells was significantly higher with the mutants, although not toxic to human PBMCs than WT. The mutants showed approximately 3-fold lower IgG and IgM production compared to WT. Pharmacokinetic study in BALB/c mice showed longer half-life of the mutants (KHY-17- 267.28±9.74; KHYW-17- 167.41±14.4) compared to WT (103.24±18). Single and repeat-doses showed no toxicity up to 2000 IU/kg and 1600 IU/kg respectively. Efficacy in ALL xenograft mouse model showed 80–90 % reduction of leukemic cells with mutants compared to 40 % with WT. Consequently, survival was 90 % in each mutant group compared to 10 % with WT. KHYW-17 showed over 2-fold lower binding to pre-existing anti-asparaginase antibodies from ALL patients treated with l-asparaginase. Conclusion: EcA variants demonstrated better pharmacological properties compared to WT that makes them good candidates for further development.